Lorecivivint, a Novel Intraarticular CDC‐like Kinase 2 and Dual‐Specificity Tyrosine Phosphorylation‐Regulated Kinase 1A Inhibitor and Wnt Pathway Modulator for the Treatment of Knee Osteoarthritis: A Phase II Randomized Trial. Issue 10 (6th September 2020) - Yazici, Yusuf; McAlindon, Timothy E.; Gibofsky, Allan; Lane, Nancy E.; Clauw, Daniel; Jones, Morgan; Bergfeld, John; Swearingen, Christopher J.; DiFrancesco, Anita; Simsek, Ismail; Tambiah, Jeyanesh; Hochberg, Marc C.
Abstract : Objective: To assess the safety and efficacy of a novel Wnt pathway modulator, lorecivivint (SM04690), for treating pain and inhibiting structural progression in moderately to severely symptomatic knee osteoarthritis (OA). Methods: Subjects in this 52‐week, phase IIa, multicenter, randomized, double‐blind, placebo‐controlled, dose‐ranging trial received a single 2‐ml intraarticular injection of lorecivivint (dose of 0.03 mg, 0.07 mg, or 0.23 mg) or placebo. Efficacy was assessed based on change from baseline on the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score subscales for pain and function (scale 0–100 for each) and change from baseline in the radiographic medial joint space width (JSW). Baseline‐adjusted analysis of covariance with multiple imputation was performed separately to evaluate efficacy. This proof‐of‐concept study evaluated the intent‐to‐treat population as well as a prespecified group of subjects with unilateral symptoms of knee OA (designated UNI) and an additional post hoc subgroup of subjects with unilateral symptoms but without widespread pain (designated UNI WP−). Results: In this trial, 455 subjects were randomized to a treatment group. The primary end point, significant improvement in the WOMAC pain score compared with placebo at week 13, was not met by any lorecivivint dose group (mean ± SD change from baseline, −23.3 ± 2.2 in the 0.03 mg group, −23.5 ± 2.1 in the 0.07 mg group, −21.3 ± 2.2 in the 0.23 mg group, and −22.1 ± 2.1 in the placebo group; each P > 0.05 versus placebo). All groups (including placebo) demonstrated clinically meaningful (≥20‐point) improvements from baseline in the WOMAC pain score. The durability of response was evaluated through week 52. In the prespecified UNI group and post hoc UNI WP− group at week 52, treatment with 0.07 mg lorecivivint significantly improved the WOMAC pain score (between‐group difference versus placebo, −8.73, 95% confidence interval [95% CI] −17.44, −0.03 [ P = 0.049] and −11.21, 95% CI −20.99, −1.43 [ P = 0.025], respectively) and WOMAC function score (between‐group difference versus placebo, −10.26, 95% CI −19.82, −0.69 [ P = 0.036] and −13.38, 95% CI −24.33, −2.43 [ P = 0.017], respectively). Relative to baseline, the mean change in the medial JSW at week 52 was −0.04 mm in the 0.03 mg cohort, −0.09 mm in the 0.07 mg cohort, −0.16 mm in the 0.23 mg cohort, and −0.14 mm in the placebo cohort; no treatment group achieved a significant change in medial JSW compared with placebo at week 52. In both unilateral symptom subgroups, the 0.07 mg lorecivivint dose significantly increased medial JSW compared with placebo at week 52 (medial JSW 0.39 mm, 95% CI 0.06, 0.72 in the UNI group [ P = 0.021] and 0.42 mm, 95% CI 0.04, 0.80 in the UNI WP− group [ P = 0.032]). Changes observed in the 0.03 mg and 0.23 mg dose groups were not significantly different from those in the placebo group for any of these measures. Lorecivivint appeared safe and well tolerated. Conclusion: This phase IIa, proof‐of‐concept trial in patients with symptomatic knee OA did not meet its primary end point. Nevertheless, the study identified a target population in whom to evaluate the potential efficacy of lorecivivint for the treatment of knee OA.